PENGARUH PENGENDALIAN INTERNAL, KOMPENSASI DAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN PADA YAYASAN MERCY INDONESIA - Marten Ngongo Nguji; I Gusti Agung Krisna Lestari (Journal Research of Accounting, 2020)
Employee performance is one of the things that needs to be considered in a company or organization. This study discusses the effect of internal control (X1) Compensation (X2 and Accounting Information Systems (X3) on employee performance (Y) on the Mercy Indonesia Foundation. The population and at the sample in this study amounted to 40 people. The data analysis technique used is, test data quality, classic assumption test, multiple liear regression analysis, t-test analysis, F-test analysis, and determination analysis.The conclusions obtained are Internal Control (X1) partial has a significant effect on employee performance (Y) on the Mercy Indonesia Foundation shown by the positive regression coefficient b1X1. Compensation (X2) partial does not have a significant effect on employee performance (Y) on Mercy Indonesia Foundation, this can be seen in the coefficient b2X2 which is negative. Accounting Information System (X3) is partial not has a significant influence on employee performance (Y) at the appointed Mercy Indonesia Foundation n by positive regression coefficient b3X3. The magnitude of the influence of internal control, compensation, and accounting information systems is 40.6% and the remaining 59.4% is influenced by other variables not examined in this study.